2018
DOI: 10.1021/acs.inorgchem.8b01407
|View full text |Cite
|
Sign up to set email alerts
|

CO Release from N,C,S-Pincer Iron(III) Carbonyl Complexes Induced by Visible-to-NIR Light Irradiation: Mechanistic Insight into Effects of Axial Phosphorus Ligands

Abstract: Light-induced CO release from newly synthesized N,C,S-pincer iron(III) carbonyl complexes with two phosphorus ligands- trans-[Fe(L-κ N,C,S)(CO)(PRR')]PF ([1]PF, R = Me, R' = Ph; [2]PF, R = R' = Me; [3]PF, R = R' = OEt)-were investigated. All the iron(III) carbonyl complexes were stable in solution and showed light-inducible CO release under ambient conditions. Studies on the wavelength dependence of photoreaction revealed that the phosphite complex [3]PF exhibited the most extended photosensitivity including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…To deliver CO effectively, safely, and controllably in clinic applications, the concept of CO-releasing molecules (CORMs), either organic compounds or transition metal carbonyls, was proposed in the beginning of this century by Motterlini et al [22] The CORMs release CO under external stimulations such as ligand exchange reaction, photon-induction, redox initiation, enzymatic triggering, and thermal decomposition. [16,20,23] Of a variety of transition metal carbonyls as potential CORMs, iron carbonyls are of particular interest in this regard, [3,[24][25][26][27] not only because iron is an essential element in human body, which may suggest that this type of carbonyls possess minimum detrimental effect compared with other transition metal carbonyls, but also iron offers tremendous options for potential CORMs because iron carbonyls are found across a wide range of oxidation states from −2 to +3. [28] In the past decade or so, we have explored iron carbonyls as potential CORMs by studying a wide range of iron carbonyls for their synthesis and decomposing behaviors, CO-releasing kinetics, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…To deliver CO effectively, safely, and controllably in clinic applications, the concept of CO-releasing molecules (CORMs), either organic compounds or transition metal carbonyls, was proposed in the beginning of this century by Motterlini et al [22] The CORMs release CO under external stimulations such as ligand exchange reaction, photon-induction, redox initiation, enzymatic triggering, and thermal decomposition. [16,20,23] Of a variety of transition metal carbonyls as potential CORMs, iron carbonyls are of particular interest in this regard, [3,[24][25][26][27] not only because iron is an essential element in human body, which may suggest that this type of carbonyls possess minimum detrimental effect compared with other transition metal carbonyls, but also iron offers tremendous options for potential CORMs because iron carbonyls are found across a wide range of oxidation states from −2 to +3. [28] In the past decade or so, we have explored iron carbonyls as potential CORMs by studying a wide range of iron carbonyls for their synthesis and decomposing behaviors, CO-releasing kinetics, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a longer reaction time was required to complete the reaction of 1 or 2 with excess of PMe 3 compared with the corresponding reaction of [Fe 2 (μ-PyBPT)(CO) 5 ]. 32 Crystal structure analysis of complexes 3 and 4 confirmed the octahedral geometry consisting of the N,C,S-tridentate ligand forming S-and N-metallacycles, a carbonyl ligand, and two axial PMe 3 ligands (Figure 3, Table 1). The benzene ring fused to the S-metallacycle and the quinoline ring fused to the N-metallacycle are in an equatorial plane; the dihedral angles are 11.9(1)°for 3 and 5.55(6)°for 4.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…These values are smaller than that between the S-bound benzene ring and the pyridine ring in trans-[Fe(PyBPT)(CO)(PMe 3 ) 2 ] (5, Figure 1a, L P = PMe 3 ) (20.63(5)°). 32 The difference is related to the planarity of the S-metallacycle in 3 and 4. The root-mean-square deviation of S-metallacycle from the least-squares plane is 0.036 Å for 3 and 0.024 Å for 4, which are significantly smaller than those for 5 (0.108 Å).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that iron carbonyls undergo photoinduced dissociation of CO and the ligand substitution reactions are faster upon irradiation . Light could promote the release of CO from 1 facilitating the insertion of the remaining CO into the Fe–C bond within a five-coordinate intermediate.…”
Section: Resultsmentioning
confidence: 99%